RARE EARTH AND RADIOACTIVE (TH, U) ELEMENTS IN THE COMPONENTS OF THE ENVIRONMENT ON THE TERRITORY OF TOMSK REGION - Natalia V. Baranovskaya; Elena V. Ageeva; Bulat R. Soktoev; Dina V. Narkovich; Olga A. Denisova; Tamara V. Matkovskaya (Известия Томского политехнического университета: Инжиниринг георесурсов, 2020)
The relevance of the research is caused by the need to consider the correlations of radioactive and rare earth elements from the point of view of their high indicator role in the complex of components of the environment in local territories characterized by different natural and man-made conditions and zoning of the territory based on biogeochemical indicators. The aim of the research is to consider the correlations of radioactive and rare earth elements in the complex of the components of the environment in the territory of the Tomsk region, characterized by various natural and man-made environments. Methods. The main method of the research is instrumental neutron activation analysis, which was carried out on the basis of a research nuclear reactor of the National Research Tomsk Polytechnic University. The content of two radioactive – thorium and uranium, as well as seven rare earth (La, Ce, Sm, Eu, Tb, Yb, Lu) elements - was determined. Results. The authors have studied the content of rare earth and radioactive elements in four simultaneously selected and studied components of the environment of Tomsk region: soil, salt sediment of water, human blood and hair. The content of the studied elements is maximal for soils and for salt sediment of water, and significantly lower in human biosubstrates. Human hair and blood as living tissues are characterized by a sharp cerium minimum. The ytterbium maximum was detected in the blood, which may be related to its presence in the form of organometallic complexes. According to the frequency of occurrence of the anomalous contents of rare earth and radioactive elements, zoning of Tomsk region was carried out for significant tributaries of the Ob river in all studied components.